1997
DOI: 10.1016/s0022-5347(01)64687-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening Cystoscopy and Survival of Spinal Cord Injured Patients With Squamous Cell Cancer of the Bladder

Abstract: Cystoscopy to screen for squamous cell cancer of the bladder in spinal cord injured patients with chronic or recurrent urinary tract infection results in an earlier stage at diagnosis and appears to convey a survival advantage. Such a protocol should be strictly followed and careful prospective studies must be performed to ascertain if this will become significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…15,16 Inflammation secondary to chronic urinary tract irritation from bacterial infections, foreign bodies, bladder calculi, or chronic bladder outlet obstruction (BOO), have been implicated in the pathogenesis of SCC. Many of these factors are present in patients with SCI and long-term indwelling catheters.…”
Section: Pathogenesismentioning
confidence: 99%
“…15,16 Inflammation secondary to chronic urinary tract irritation from bacterial infections, foreign bodies, bladder calculi, or chronic bladder outlet obstruction (BOO), have been implicated in the pathogenesis of SCC. Many of these factors are present in patients with SCI and long-term indwelling catheters.…”
Section: Pathogenesismentioning
confidence: 99%
“…Pathological and epidemiological studies (Kaufman et al, 1977;El-Masri and Fellows, 1981;Sakamoto et al, 1992;Navon et al, 1997) have indicated that squamous metaplasia is a premalignant lesion of SCC of the bladder, however its genetic alterations have not been previously analysed. In this study, squamous metaplasias from bladder cancer patients showed frequent (45%) homozygous deletions of p16/p19 and LOH of 9p21.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous metaplasia of the bladder is a condition in which normal transitional epithelium is replaced by metaplastic squamous epithelium, and is often observed in patients with indwelling catheters or those with chronic or recurrent infections (Kaufman et al, 1977;El-Masri and Fellows, 1981;Navon et al, 1997). This mucosal change is frequently observed in patients with spinal cord injuries, who have a 16 ± 28 times increased risk of squamous cell carcinoma of the bladder (Kaufman et al, 1977;El-Masri and Fellows, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…13 The incidence of bladder cancer increased in SCI survivors and occurs at a younger age compared to the general population. Risk factors include recurrent urinary tract infections, bladder calculi and/or diverticuli and long use of an indwelling catheter 23,24 In patients treated with long-term indwelling catheter, the incidence of squamous cell carcinoma is at least 20 times more than in the general population. 23 Regular cystoscopy can be effective in detecting early bladder carcinoma.…”
Section: Urinary Systemmentioning
confidence: 99%
“…23 Regular cystoscopy can be effective in detecting early bladder carcinoma. 24 Longstanding paraplegia is characterized by a high percentage of secondary structural changes in the urinary tract, especially at the bladder outlet. Once these changes are established, the outflow resistance is further increased, highlighting the need for regular lifelong monitoring and early adequate management of functional outflow obstruction, based on careful clinical and urodynamic evaluation before secondary structural changes are established.…”
Section: Urinary Systemmentioning
confidence: 99%